A multi-institutional analysis of prospective studies of carbon ion radiotherapy for prostate cancer: A report from the Japan Carbon ion Radiation Oncology Study Group (J-CROS). Issue 2 (November 2016) - Nomiya, Takuma; Tsuji, Hiroshi; Kawamura, Hidemasa; Ohno, Tatsuya; Toyama, Shingo; Shioyama, Yoshiyuki; Nakayama, Yuko; Nemoto, Kenji; Tsujii, Hirohiko; Kamada, Tadashi
Abstract: Background and purpose: A multi-institutional observational study (J-CROS1501PR) has been carried out to analyze outcomes of carbon-ion radiotherapy (CIRT) for patients with prostate cancer. Patients and methods: Data of the patients enrolled in prospective studies of following 3 CIRT institutions were analyzed: National Institute of Radiological Sciences (NIRS; Chiba, Japan), Gunma University Heavy Ion Medical Center (GHMC; Gunma, Japan), and Ion Beam Therapy Center, SAGA HIMAT Foundation (HIMAT; Saga, Japan). Endpoints of the clinical trial are biochemical recurrence-free survival (bRFS), overall survival (OS), cause-specific survival (CSS), local control rate (LCR), and acute/late adverse effects. Results: A total of 2157 patients' data were collected from NIRS ( n  = 1432), GHMC ( n  = 515), and HIMAT ( n  = 210). The number of patients in low-risk, intermediate-risk, and high-risk groups was 263 (12%), 679 (31%), and 1215 (56%), respectively. The five-year bRFS in low-risk, intermediate-risk, and high-risk patients was 92%, 89%, and 92%, respectively. The five-year CSS in low-risk, intermediate-risk, and high-risk patients was 100%, 100%, and 99%, respectively. The incidence of grade 2 late GU/GI toxicities was 4.6% and 0.4%, respectively, and the incidence of ⩾G3 toxicities were 0%. Conclusions: Favorable overall outcomes of CIRT for prostate cancer were suggested by the analysis of the first multi-institutional data.